2020
DOI: 10.7717/peerj.9996
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell landscape analysis reveals prognostic immune cells and its potential mechanism in squamous cell lung carcinoma

Abstract: Background Squamous cell lung carcinoma (LUSC) was closely associated with smoking which was known to have a distant immunosuppression effect. In this study, we aimed to explore the relationship between immune cells and clinical outcomes of LUSC patients with smoking history. Methods The immune cell infiltration and RNA expression profiles of LUSC patients were collected from The Cancer Genome Atlas (TCGA). Then, the correlation between imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The lung microenvironment promotes the carcinogenesis of LUSC, including inflammation, angiogenesis, immune modulation or inhibition, and response or resistance to therapies ( Altorki et al, 2019 ). Yongyong Wang et al demonstrated that immune cell infiltrations are associated with the prognosis in squamous cell lung carcinoma ( Wang and Guo, 2020 ). The immune landscape accurately provides the development and immunotherapy status of LUSC ( Zhao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lung microenvironment promotes the carcinogenesis of LUSC, including inflammation, angiogenesis, immune modulation or inhibition, and response or resistance to therapies ( Altorki et al, 2019 ). Yongyong Wang et al demonstrated that immune cell infiltrations are associated with the prognosis in squamous cell lung carcinoma ( Wang and Guo, 2020 ). The immune landscape accurately provides the development and immunotherapy status of LUSC ( Zhao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wasén et al found that smoking induces the apoptosis of CD4 + T cells in patients with rheumatoid arthritis [ 38 ]. Furthermore, Wang and Guo found decreased infiltration of resting memory CD4 T cells and increased infiltration of follicular helper T cells in patients with lung squamous cell cancer who smoked or had quit smoking for less than 15 years [ 39 ]. The results of our study are consistent with those of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tfh cells are reported to show more significant infiltration in current smokers and LUSC current reformed smokers who have been smoking for less than 15 years, whereas resting memory CD4 T cells had reduced infiltration. Tfh cell infiltration has been linked to a higher overall survival (OS) rate; however, the relationship varied depending on the TNM stage ( 118 ).…”
Section: Lncrnas In Luscmentioning
confidence: 99%